Synthesis of AlOxNy thin films using a two-step PE-ALD process - Mohammed Zeghouane; Pedro Fernandes Paes Pinto Rocha; Sarah Boubenia; Franck Bassani; Gauthier Lefevre; Sebastien Labau; Laura Vauche; Eugénie Martinez; Marc Veillerot; Bassem Salem (AIP Advances, 2023)
Homogeneous AlOxNy thin films with a controlled nitrogen composition, up to 7.1%, were grown on GaN substrate using plasma-enhanced atomic layer deposition. This was achieved through repeated cycles consisting of AlN thin layers deposition and subsequent in situ O2 plasma oxidation under optimized conditions. We demonstrate that the nitrogen concentration in AlOxNy films can be finely tuned from 1.5% to 7.1% by a precise control of the AlN thin film thickness from 0.25 to 0.96 nm before each oxidation step. It is shown also that higher AlN thickness, ≥1.96 nm, leads to an incomplete plasma oxidation of AlN films, resulting in the formation of AlOxNy/AlN-like structures. Several structural and physic-chemical characterizations, including focused ion beam-scanning transmission electron microscopy, Auger electron spectroscopy, XPS, and time-of-flight secondary ion mass spectrometry were performed to confirm these findings. These results highlight the importance of this approach for growing homogeneous AlOxNy thin films with controlled nitrogen doping, which can be used as dielectrics in gate stacks for high performance GaN-based transistors.